1982
DOI: 10.1093/ee/11.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Biotype Populations 2 and 3 of Nilaparvata lugens1 by Exposure to Resistant Rice Varieties

Abstract: The release of an insect pest-resistant variety and subsequent adaptation of the insect species to that variety through the process of biotype selection has occurred on many cultivated crops. The present study was designed to obtain detailed information on some of the processes involved in the selection of biotypes of Nilaparvata lugens (Stål) on two rice varieties with different major genes for resistance. The N. lugens population selected for the study, which had originally been collected in the field and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 9 publications
3
53
0
Order By: Relevance
“…In so doing, estimates ofthe magnitude of quantitative genetic variation in host plant related characters were produced. These parametric estimates supplement the qualitative evidence, chiefly from population crosses and selection experiments, that characters associated with host plant use in herbivores and pathogens are indeed genetically based (Smith, 1941;Gallun et al, 1961;Hatchett and Gallun, 1970;Knerer and Atwood, 1973;Day, 1974;Groth and Person, 1977;Gould, 1979;Wasserman and Futuyma, 1981;Pathak and Heinrichs, 1982;Jaenike and Grimaldi, 1983;Futuyma et al, 1984). The study of genetic mechanisms of insect-host plant evolution requires quantitative estimates of several popu- The genotype-environment interaction estimated here in development time on different host plants (Table 3-5) demonstrates that genetic variation in the relative performance of individuals on different host plants can occur within a "generalist" species.…”
Section: Discussionmentioning
confidence: 63%
“…In so doing, estimates ofthe magnitude of quantitative genetic variation in host plant related characters were produced. These parametric estimates supplement the qualitative evidence, chiefly from population crosses and selection experiments, that characters associated with host plant use in herbivores and pathogens are indeed genetically based (Smith, 1941;Gallun et al, 1961;Hatchett and Gallun, 1970;Knerer and Atwood, 1973;Day, 1974;Groth and Person, 1977;Gould, 1979;Wasserman and Futuyma, 1981;Pathak and Heinrichs, 1982;Jaenike and Grimaldi, 1983;Futuyma et al, 1984). The study of genetic mechanisms of insect-host plant evolution requires quantitative estimates of several popu- The genotype-environment interaction estimated here in development time on different host plants (Table 3-5) demonstrates that genetic variation in the relative performance of individuals on different host plants can occur within a "generalist" species.…”
Section: Discussionmentioning
confidence: 63%
“…Mass-rearing inbred BPH populations established on TN1, Mudgo, and ASD7 were designated as biotypes 1, 2, and 3 at IRRI (IRRI 1976;Pathak and Heinrichs 1982). So far as these biotypes 1, 2, and 3 concern, they show phenotypically a vertical virulence specific to the BPH resistance genes Bph1 and bph2, as if there were a gene-for-gene relationships between the virulence of biotypes and host plant resistance conferred by each BPH resistance gene (Gallun and Khush, 1980).…”
Section: Varietal Resistance-breaking Planthopper Biotypesmentioning
confidence: 99%
“…Selection experiments revealed that BPH populations could easily adapt to the resistance varieties carrying the Bph1 and bph2 genes within 5-10 generations under continuous inbred conditions (Clarige and Den Hollander 1982;Pathak and Heinrichs 1982;Sogawa and Kilin 1987). Heritability for BPH biotypes is estimated based on the data of selection experiments.…”
Section: Genetic Flexibility In the Bph Biotype Populationsmentioning
confidence: 99%
“…Some differences between populations have been shown to be genetically determined (e.g., Hsiao, 1978;Tabashnik, ~ 1983;Thind & Muggleton, 1981;Rausher, 1982;Scriber, 1982;Bowers, 1986;Thomas et al, 1987). Nonetheless, only a few studies have demonstrated a genetic basis for within-population variation in oviposition preference (e.g., Jaenike & Grimialde, 1983;Thompson, 1988) or performance (e.g., Gallun et al, 1961;Gould, 1979;Pathak & Heinrichs, 1982;Tabashnik, 1983;Rausher, 1984a;Hare & Kennedy, 1986). Moreover, nearly nothing is known about how these aspects of host use covary genetically (Via, 1986).…”
Section: Genetic Covariance In Preference and Performancementioning
confidence: 99%